Stylistic Features of Poems Reflecting the Image of a Woman by Halima Khudoyberdiyeva (Multidisciplinary Journal of Science and Technology, 2024)
This article analyzes the stylistic features of the female image in the work of the poetess and her place in society, social role, inner world, feelings, and dreams. The poetess describes the woman through metaphors, symbolic images and realism, clearly and inspiringly reflects her love, sorrow and changes. Khudoyberdiyeva sheds light on a woman's spiritual quest, family relationships, and place in society, as well as her social struggles and dreams.